3x*2x-1=18*6

Simple and best practice solution for 3x*2x-1=18*6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x*2x-1=18*6 equation:


Simplifying
3x * 2x + -1 = 18 * 6

Reorder the terms for easier multiplication:
3 * 2x * x + -1 = 18 * 6

Multiply 3 * 2
6x * x + -1 = 18 * 6

Multiply x * x
6x2 + -1 = 18 * 6

Reorder the terms:
-1 + 6x2 = 18 * 6

Multiply 18 * 6
-1 + 6x2 = 108

Solving
-1 + 6x2 = 108

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + 6x2 = 108 + 1

Combine like terms: -1 + 1 = 0
0 + 6x2 = 108 + 1
6x2 = 108 + 1

Combine like terms: 108 + 1 = 109
6x2 = 109

Divide each side by '6'.
x2 = 18.16666667

Simplifying
x2 = 18.16666667

Take the square root of each side:
x = {-4.262237285, 4.262237285}

See similar equations:

| 19x+3(4x+9)=-6x-38 | | 7(2a-5)=-21 | | -x+27=-6.8 | | 5(4x+8)=120 | | 8(6+2f)=128 | | 5(6y-2)=20 | | 4(5c+15)=20 | | 3(9-2b)=3 | | 6(5+a)=54 | | 21y^2+46y+20=0 | | 5(5x+1)=105 | | y=7+x/14 | | 2(3y+4)=2 | | 2(2d+3)=34 | | 10.8k= | | 2(3x+5)=27 | | 850=x+(x*.1) | | G(t)=-15t^2+240t-951 | | y=-2(1,7) | | x/8=x+180/20 | | x/8=x+11180/20 | | 9x^2-38x+1=0 | | 1.1x-3.3= | | 400x-2000x^2+10=0 | | f(X)=(x+4)-2 | | 0.8x+.7=6.3 | | 0.8x+.07=6.3 | | 2.7=8.2+y | | 7/6c=3/5 | | p/-4=-63 | | -3/2m=7 | | y^3*3= |

Equations solver categories